2018
DOI: 10.1590/1807-2577.06817
|View full text |Cite
|
Sign up to set email alerts
|

Structural factors for public dental health services in Regional Health Care Network 13: an analysis of the Brazilian National Program for Improving Access and Quality of Primary Care

Abstract: Introduction The Brazilian National Program for Improving Access and Quality of Primary Care aims to induce the institution of processes that expand the capacity of federal, state and municipal administrations and Primary Care teams to offer services that ensure greater access and quality. Objective To identify the characteristics of infrastructure for the dental health care of the health units from the Regional Health Care Network 13, from the perspective of a health evaluation. Material and method This is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
4
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 17 publications
4
4
0
1
Order By: Relevance
“…A greater amount of dental equipment favored the offer of first dental appointments. This association has also been reported in previous studies [24,25]. The ratio between completed treatments and first scheduled dental appointments was also favored as the number of supplies…”
Section: Discussionsupporting
confidence: 86%
“…A greater amount of dental equipment favored the offer of first dental appointments. This association has also been reported in previous studies [24,25]. The ratio between completed treatments and first scheduled dental appointments was also favored as the number of supplies…”
Section: Discussionsupporting
confidence: 86%
“…Equipment, such as face shields, disposable aprons, and N95 masks, are now included in a new work routine and infection control that will challenge all dental services in both the world and the OHT in PHC in Brazil [ 14 , 15 ]. Previous studies identified differences between macroregions in the process of dental infection control in public services [ 16 ]. In this study, the South region had the best infection control structure, while the North region had the worst structure, corroborating previous national findings [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies identified differences between macroregions in the process of dental infection control in public services [ 16 ]. In this study, the South region had the best infection control structure, while the North region had the worst structure, corroborating previous national findings [ 16 ]. Studies show that Brazil is a country marked by regional socioeconomic inequalities that impact health [ 7 , 17 ] and that the country's health policies should be reoriented to minimize such inequities [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations